The Role of Agriculture Cooperatives for Farmer Empowerment: A Literature Review and Its Implications on Poverty - Intan Mala Sari; Sulaeman Rahman Nidar; Rita Komaladewi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study examines the role of agricultural cooperatives in empowering farmers and alleviating poverty in rural areas. Despite their potential, cooperatives face several challenges that hinder their effectiveness, especially in developing countries. This study aims to evaluate the contributions of agricultural cooperatives in improving farmers' access to finance, technology, and markets, and how they support integration into modern agricultural systems. A literature review approach based on the PRISMA method and bibliometric analysis was employed, identifying 157 relevant articles published between 2005 and 2024. The findings reveal that agricultural cooperatives significantly reduce multidimensional poverty in countries like China and Tanzania by improving material and social well-being. However, challenges such as low organizational capacity, uneven benefit distribution, and inadequate policy support persist. The study also highlights gaps in adapting cooperative models to local socio-economic contexts. Future research should focus on adapting suitable technologies, strengthening partnerships with smallholder farmers, and evaluating the role of government policies in fostering cooperative ecosystems. This study offers insights into the potential of cooperatives.as a tool for economic empowerment and offers suggestions for future research on inclusive and sustainable rural development.